Interaction of artocarpus lectins with human-iga does not involve asparagine-linked oligosaccharide of the immunoglobulin - Hashim, Onn Haji; Kobayashi, K.; Taniguchi, N. (1992)
In view of the controversy with respect to the interaction of jacalin with human IgA2, a study was undertaken to assess the reactivity of the Artocarpus heterophyllus lectin, as well as the lectin from Artocarpus integer (lectin C), with subclasses of human immunoglobulin A by ELISA. Our data is consistent with the view that Artocarpus lectins have no affinity for the IgA2 immunoglobulins. In further support of the findings, we have established that N-linked oligosaccharide moieties of IgA have no significant bearing in the lectin-immunoglobulin binding. Interaction was also not affected in the presence of 1 (w/v) BSA.